UK media representations of carbon capture and storage: actors, frames and metaphors - Nerlich, Brigitte; Jaspal, Rusi (John Benjamins, 2013)
Carbon Capture and Storage (CCS) is a climate change mitigation technology which has had a rather chequered history in British policy making and in the British public sphere. This article deals with the neglected topic of representations of CCS in the British media and their possible impact on public perceptions and public policy. Public perception of CCS is shaped in part by the media which provide tools for making sense of complex technological and political issues such as CCS. This article compares articles on CCS in two UK newspapers, one national (“The Times”) and one regional (“The Aberdeen Press and Journal”) in 2011, a year during which some of the last battles over CCS demonstration projects were fought. It applies frame and metaphor analysis to a corpus of 150 articles. Findings reveal that during 2011 CCS coverage moved through a cycle of hype and disillusionment, with both newspapers reaching a trough of disappointment at the end of 2011. It will be difficult to reignite interest in CCS in this context, both in terms of media and public attention, and in terms of policy and investment. Regional confidence in national CCS policy in particular will be difficult to recover.